Proposta de dicionário infantil bilíngue libras/ português - Klimsa, Severina Batista de Farias (2016)
Dictionaries are important works for the lexicon registry of different languages, whether oral or visual, and the school context. The Brazilian Sign Language (Libras) has a long tradition in the production of dictionaries. The aim of our thesis is to propose a model of bilingual children's dictionary Libras / Portuguese for the deaf children in early literacy process of the first year of elementary school 1. For the development of this proposal, we follow the guidelines established by the National Textbook Program ( PNLD) for dictionaries type 1. Initially, to understand the lexical choices adopted by the authors, conducted a survey in dictionaries: My First Dictionary Caldas Aulete with the class of Cocoricó, My First Dictionary Saraiva the Portuguese Language and Blucher Illustrated children's Illustrated, projects approved and appropriate to the school context by its program. Our corpus consists of 500 entries belonging to the infant universe, selected from Deit-Libras: Encyclopedic Dictionary Illustrated Trilingual the Brazilian Sign Language (2001) and the three volumes of the Illustrated Book of Brazilian Sign Language: unmasking communication (2009). The research is inserted in the lexicography of the fields according to the study Biderman (1998), Carvalho (2001), Barros (2004), and Libras with Felipe works (1989), Quadros and Karnopp (2004) and Ferreira- Brito (2010). The results demonstrate that the creation of this type of work in Libras is possible, because it will contribute to the educational development of deaf children and as a teaching resource to support the teachers working in the classroom.